Application of Seafloor Mapping Technology for Search and Rescue: AirAsia QZ8501 Case Study - Rahadian Rahadian; Muhammad Irfan; Athur Yordan; Taufan Wiguna; Ouzani Bachir (Indonesian Journal of Physics, 2015)
Seafloor mapping shows size, position, and depth of morphology and any objects at seafloor. Therefore, these technologies can be used to search and rescue (SAR) which are applied when AirAsia QZ8501 was missing at southern Karimata Strait using three vessels, RV. Baruna Jaya I, MV. Java Imperia, and KN. Trisula. Seafloor mapping technologies that applied were (i) multibeam echosounder system (MBES), (ii) side scan sonar (SSS), (iii) magnetometer (MM), (iv) autonomous underwater vehicle (AUV), (v) pinger locator (PL), (vi) underwater remotely operated vehicles (ROV). MBES, SSS, AUV, and USBL use acoustic wave that transmitted by transducer to seafloor then it back to reciever. Indirectly, MBES and SSS generate 3D image based on acoustics signal according to sound propagation and its travelling time in sea from transducer to receiver. MBES and SSS transmit acoustic wave with frequency 180 kHz for MBES and dual-frequency (120 kHz and 420 kHz) for SSS. AUV that attached SSS working with frequency 600/1600 kHz. USBL that used as pinger locator transmit acoustic wave with same frequency as blackbock which known using 37.5 kHz. USBL inform distance between transducer to blackbox, so that the position of blackbock can be determined by triangulation method. MBES and SSS on KR. Baruna Jaya I detect suspect anomaly with height about 3 meters. SSS that installed on AUV and operated on KN Trisula detect an object looks like human body. Triangulation method was done on MV. Java Imperia has found blackbox position.